The Relationship Between Managerial Support and Nurse Burnout - Fadila Nurlita Septiani; Iyos Sutresna; Heri Ridwan (Genius Journal, 2026)
Introduction: Burnout among nurses remains a major challenge in healthcare systems worldwide, particularly in inpatient settings with high workload demands such as surgical wards. Managerial support plays an important role in shaping the work environment, including the provision of adequate facilities that enable nurses to perform their duties effectively. Insufficient facilities may increase work strain and contribute to burnout. Objective: This study aimed to examine the relationship between managerial support in facility provision and burnout among nurses working in surgical inpatient wards. Method: A quantitative correlational study with a cross-sectional design was conducted among nurses in surgical inpatient wards at a public hospital. Total sampling was applied, involving 33 nurses who met the inclusion criteria. Data were collected using a managerial support in facility provision questionnaire and the Maslach Burnout Inventory. The instruments demonstrated acceptable validity and reliability. Data were analyzed using descriptive statistics and Spearman correlation analysis. Result: The findings showed that most nurses perceived managerial support in facility provision at moderate to high levels, while burnout levels among nurses were predominantly moderate to high. Spearman correlation analysis indicated that there was no significant relationship between managerial support in facility provision and burnout (p > 0.05). Conclusion: Managerial support in providing adequate facilities is significantly associated with burnout among nurses in surgical inpatient wards. Enhancing managerial support for facility provision may contribute to reduced burnout and improved nurse well-being and performance.